2020
DOI: 10.3390/ijms21155195
|View full text |Cite
|
Sign up to set email alerts
|

Platelets Extracellular Vesicles as Regulators of Cancer Progression—An Updated Perspective

Abstract: Extracellular vesicles (EVs) are a diverse group of membrane-bound structures secreted in physiological and pathological conditions by prokaryotic and eukaryotic cells. Their role in cell-to-cell communications has been discussed for more than two decades. More attention is paid to assess the impact of EVs in cancer. Numerous papers showed EVs as tumorigenesis regulators, by transferring their cargo molecules (miRNA, DNA, protein, cytokines, receptors, etc.) among cancer cells and cells in the tumor microenvir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 114 publications
(161 reference statements)
0
37
0
Order By: Relevance
“…EVs are a diverse group of membrane-enclosed structures, released from cells to bloodstream in physiological and pathological conditions [ 55 ]. EVs act on target cells by delivering ligands and signaling complexes.…”
Section: Role Of Platelet-derived Extracellular Vesicles In Atheromentioning
confidence: 99%
See 1 more Smart Citation
“…EVs are a diverse group of membrane-enclosed structures, released from cells to bloodstream in physiological and pathological conditions [ 55 ]. EVs act on target cells by delivering ligands and signaling complexes.…”
Section: Role Of Platelet-derived Extracellular Vesicles In Atheromentioning
confidence: 99%
“…EVs act on target cells by delivering ligands and signaling complexes. For example, EVs transfer microRNAs and transcription factors that epigenetically reprogram the target cells [ 55 ]. EVs are shed by cells into the extracellular space during activation, maturation, proliferation, stress, aging, or apoptosis [ 56 ].…”
Section: Role Of Platelet-derived Extracellular Vesicles In Atheromentioning
confidence: 99%
“…Compared to non-malignant cells, cancer cells have been found to increase the amount of EVs produced [18] , [19] , [20] , shift the subtype of EVs that they secrete [21] , and/or alter the cargo molecules that are selected for expulsion [ 2 , 22 , 23 ]. Of note, education by tumor cells can also affect the secretion rate and the content of EVs derived from platelets [24] , as well as noncancer cells in the TME [8] , but in this review we chose to focus on EV secretion from cancer cells only. Theoretically, both changes in content and secretion rate could contribute to the oncogenic effects of tumor-derived EVs; increased secretion of EVs with unchanged composition could drive overstimulation of recipient cells, whereas changes in EV composition, by altering EV subtype or cargo loading, could bring about tumor-supportive microenvironmental remodeling.…”
Section: Oncogenes and Tumor Suppressors Governing Ev Secretionmentioning
confidence: 99%
“…Recent evidence has shown that platelets can have a bimodal effect in colorectal cancer where they inhibit growth but promote metastasis [ 52 ]. An extensive review of the role of PMPs in cancer progression can be found elsewhere [ 53 ].…”
Section: Discussionmentioning
confidence: 99%